Efficacy of combination therapy with omeprazole, amoxicillin and clarithromycin for treatment of patients with Helicobacter pylori associated gastritis and duodenal ulcer disease - , Yeşim ERALP, Can DAVUTOĞLU, Hülya UZUNİSMAİL, Ergun OKTAY (Turkish Journal of Gastroenterology 1, 2019)
-